Heart over mind: metabolic control of white adipose tissue and liver - Michinari Nakamura; Junichi Sadoshima (EMBO Molecular Medicine, 2014)
Abstract Increasing evidence suggests that the heart controls the metabolism of peripheral organs. Olson and colleagues previously demonstrated that miR‐208a controls systemic energy homeostasis through the regulation of MED13 in cardiomyocytes (Grueter et al, 2012). In their follow‐up study in this issue of EMBO Molecular Medicine, white adipose tissue (WAT) and liver are identified as the physiological targets of cardiac MED13 signaling, most likely through cardiac‐derived circulating factors, which boost energy consumption by upregulating metabolic gene expression and increasing mitochondrial numbers (Baskin et al, 2014). In turn, increased energy expenditure in WAT and the liver confers leanness. These findings strengthen the evidence of metabolic crosstalk between the heart and peripheral tissues through cardiokines and also set the stage for the development of novel treatments for metabolic syndrome.